2007
DOI: 10.1089/neu.2006.0208
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Axonal Injury in Severe Traumatic Brain Injury Visualized Using High-Resolution Diffusion Tensor Imaging

Abstract: Traumatic brain injury (TBI) is the most common cause of death and disability in young people. The functional outcome in patients with TBI cannot be explained by focal pathology alone, and diffuse axonal injury (DAI) is considered a major contributor to the neurocognitive deficits experienced by this group. The aim of the present study was to investigate whether diffusion tensor imaging (DTI) offers additional information as to the extent of damage not visualized with standard magnetic resonance imaging (MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
130
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 35 publications
14
130
0
3
Order By: Relevance
“…DWI measures the motion of water molecules within the brain. As this diffusion is restricted by biological barriers and other molecules, abnormalities in DWI may reflect microscopic alterations to tissue organization due to factors such as white matter injury,35, 36 edema,37 and gliosis 38. Indeed, preliminary preclinical studies suggest that DWI may be a useful biomarker of mTBI23 and repeated mTBI 39, 40.…”
Section: Discussionmentioning
confidence: 99%
“…DWI measures the motion of water molecules within the brain. As this diffusion is restricted by biological barriers and other molecules, abnormalities in DWI may reflect microscopic alterations to tissue organization due to factors such as white matter injury,35, 36 edema,37 and gliosis 38. Indeed, preliminary preclinical studies suggest that DWI may be a useful biomarker of mTBI23 and repeated mTBI 39, 40.…”
Section: Discussionmentioning
confidence: 99%
“…The corpus callosum is an area known to be involved in TBI. 7,16,17,[25][26][27][28][29][30] Several studies have demonstrated increased MD and/or decreased FA in various white matter regions among patients with mild TBI versus matched control subjects. 7,17,31 Inglese et al 17 found a significant reduction in FA in the corpus callosum, internal capsule, and centrum semiovale and a significant increase in MD in the corpus callosum and internal capsule in 46 patients with mild TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Because DTI is sensitive to microstructural changes in white matter, this technique is often used to investigate white matter integrity in patients with TBI. [11][12][13][14][15][16][17] Previous studies have found that fractional anisotropy (FA) values in the corpus callosum, 14,16,17 internal capsule, 11,14,16,17 cingulum, 14 and centrum semiovale 11,14,16,17 are decreased in patients with TBI versus healthy control subjects. A longitudinal TBI study found that FA was decreased in the white matter of study participants because of decreased longitudinal diffusivity (LD) and increased transversal diffusivity (TD).…”
mentioning
confidence: 99%
“…In a rodent TBI model, axonal injury was the most prominent feature following blast exposure (Garman et al, 2011). In humans, the subsequent tissue injury is characterized by axonal stretching, inflammation, disruption, and separation of nerve fibers, although axotomy is relatively rare in even severe TBI (Adams et al, 1989;Basser and Pierpaoli, 1996;Gennarelli et al, 1982;Xu et al, 2007). Conventional CT and MRI are primarily sensitive to blood from nearby torn capillaries, rather than axonal damage itself, hence they underestimate the presence of DAI, especially in mTBI.…”
Section: Clinicalmentioning
confidence: 99%